1994
DOI: 10.1038/370295a0
|View full text |Cite
|
Sign up to set email alerts
|

Prion protein is necessary for normal synaptic function

Abstract: The prion diseases are neurodegenerative conditions, transmissible by inoculation, and in some cases inherited as an autosomal dominant disorder. They include Creutzfeldt-Jakob disease in humans and scrapie and bovine spongiform encephalopathy in animals. The prion consists principally of a post-translationally modified form of a host-encoded glycoprotein (PrPC), designated PrPSc (ref. 1); the normal cellular function of PrPC is, however, unknown. Although PrP is highly conserved among mammals and widely expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
416
4
16

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 723 publications
(453 citation statements)
references
References 21 publications
17
416
4
16
Order By: Relevance
“…Consistent with our observations in the PRNP −/− cattle, Prnp −/− mice with exclusive disruption on the Prnp ORF remained healthy 2,3 and showed only slightly abnormal phenotypes, such as altered synaptic function 29,30 and sleep-wake circadian rhythms 31,32 . However, the phenotype in the synaptic function appears to be normal in other murine genetic backgrounds 33 .We have monitored sleep-wake activity in the knockout cattle, along with age-, sex-and breed-matched wild-type controls, at frequent intervals throughout the day and night for one week, but did not observe any obvious alterations.…”
supporting
confidence: 90%
“…Consistent with our observations in the PRNP −/− cattle, Prnp −/− mice with exclusive disruption on the Prnp ORF remained healthy 2,3 and showed only slightly abnormal phenotypes, such as altered synaptic function 29,30 and sleep-wake circadian rhythms 31,32 . However, the phenotype in the synaptic function appears to be normal in other murine genetic backgrounds 33 .We have monitored sleep-wake activity in the knockout cattle, along with age-, sex-and breed-matched wild-type controls, at frequent intervals throughout the day and night for one week, but did not observe any obvious alterations.…”
supporting
confidence: 90%
“…No abnormalities were noted in Prnp °l° mice at the macroscopic, microscopic or behavioral levels [41]. The suggestion that there may be a synaptic deficiency in Prnp °/° mice [42,43] has not been confirmed [44]. The claim that aged mice (with a mixed genetic background) develop ataxia and suffer a loss of Purkinje cells [45] as a consequence of PrP gene disruption is not consistent with previous investigations on independently generated Prnp °/° mouse lines [41,46].…”
Section: Resistance To Scrapie Of Mice Devoid Of Prp Cmentioning
confidence: 99%
“…the events leading to vacuolization and neuronal death are not yet well understood. Because neurons (and astrocytes) may be depleted of PrP c, it has been speculated that this may be the cause of cell damage [42]. The fact that PrP knockout animals show no scrapie-like symptoms and appear quite healthy would argue against this hypothesis, unless one postulates that chronic deprivation of PrP allows for the recruitment of compensatory mechanisms while acute depletion, as may occur in scrapie, does not.…”
Section: Mechanism Of Pathogenesismentioning
confidence: 99%
“…In addition, PrP c , by Cu 2+ binding, may participate in the control of calcium flux and redox stage of the presynaptic terminal (Vassallo and Herms, 2003). Lastly, pioneering electrophysiological studies (using PrP c knockout slices) by Collinge established that PrP c participates in long-term potentiation (Collinge et al, 1994;Curtis et al, 2003;Maglio et al, 2006). More recently, it has been shown that the absence of PrP c alters the expression of several neurotransmitter receptors (see (Maglio et al, 2004;Rangel et al, 2007) for examples).…”
Section: Introductionmentioning
confidence: 99%